Draft Genome of the Sea Cucumber Holothuria glaberrima, a Model for the Study of Regeneration - Medina-Feliciano, Joshua G.; Pirro, Stacy; García-Arrarás, Jose E.; Mashanov, Vladimir; Ryan, Joseph F. (Frontiers in Marine Science, 2021)
Regeneration is one of the most fascinating and yet least understood biological processes. Echinoderms, one of the closest related invertebrate groups to humans, can contribute to our understanding of the genetic basis of regenerative processes. Among echinoderms, sea cucumbers have the ability to grow back most of their body parts following injury, including the intestine and nervous tissue. The cellular and molecular events underlying these abilities in sea cucumbers have been most extensively studied in the species Holothuria glaberrima. However, research into the regenerative abilities of this species has been impeded due to the lack of adequate genomic resources. Here, we report the first draft genome assembly of H. glaberrima and demonstrate its value for future genetic studies. Using only short sequencing reads, we assembled the genome into 89,105 scaffolds totaling 1.1 gigabases with an N50 of 25 kilobases. Our BUSCO assessment of the genome resulted in 894 (91.4%) complete and partial genes from 978 genes queried. We incorporated transcriptomic data from several different life history stages to annotate 51,415 genes in our final assembly. To demonstrate the usefulness of the genome, we fully annotated the melanotransferrin (Mtf) gene family, which have a potential role in the regeneration of the sea cucumber intestine. Using these same data, we extracted the mitochondrial genome, which showed high conservation to that of other holothuroids. Thus, these data will be a critical resource for ongoing studies of regeneration and other studies in sea cucumbers.